2019
DOI: 10.11591/ijeecs.v15.i1.pp328-335
|View full text |Cite
|
Sign up to set email alerts
|

Cloud based secured framework for implementation of online voting system

Abstract: <p>Accessing and Utilization of data and information from remote location is one of the major requirements of present world. Due to the increase in the requirement of the data access from remote locations, challenges in the enhancement of technology based systems also have increased proportionately. Technology based solution for accessibility of remote data with available infrastructure is the need of the hour. Implementation of technology based solutions for the challenges may be expensive due to the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…It can be observed that marriage and work are the two mains factors for migration during the last decade. Work and marriage are the major factors for migrations from the perspective of males and females respectively [11]. Security of the system using online or offline approach in computing environment is an important and critical challenge which has to be dealt with to overcome the threats and vulnerabilities that can cause damage to the system [12].…”
Section: Literature Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that marriage and work are the two mains factors for migration during the last decade. Work and marriage are the major factors for migrations from the perspective of males and females respectively [11]. Security of the system using online or offline approach in computing environment is an important and critical challenge which has to be dealt with to overcome the threats and vulnerabilities that can cause damage to the system [12].…”
Section: Literature Surveymentioning
confidence: 99%
“…The key tasks carried in the designed cloud framework are: i) K1: encryption of ticket at the controller; ii) K2: decryption of ticket at the cloud; iii) K3: encryption of ACK at the cloud; iv) K4: decryption of ACK at the controller [11]. Performance analysis of three algorithms implemented on the designed framework is carried out by recording the readings of the execution time of five hundred voters on a predefined software and hardware environment.…”
Section: Performance Analysis Of Key Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested framework can promote confidentiality under privacy protection, especially in the cloud mobile computing environment. The work in K. S. Gururaj and K. Thippeswamy[32] is a cloud-based secured framework for utilization in an online voting system. The paper examined the present trend of accessing information from remote locations, which has attendant challenges on data access, especially on the cloud.…”
mentioning
confidence: 99%